Estudo exploratório de um sensor de deformação utilizando nanotubos de carbono para materiais cimentícios - Lucas Freitas de Pinho Tavares (2020)
To guarantee the safety of any building structure, a Structural Health Monitoring (SHM) system is essential. In Brazil, a common situation is the deterioration of infrastructure and/or continuous use of it after the end of the life span. A Structural Health Monitoring system can help the country’s infrastructure fulfill its expected performance with safety. In an SHM system, a sensor has the purpose of providing information on the deformations of an element that is part of the structure. This study aims to explore a strain gage using carbon nanotubes (CNT). This fact is based on the CNT piezoresistivity property: the CNT electrical resistance is related to its current strain state. Mechanical tests were performed using prismatic mortar specimens, applying the CNT sensor at one face and an electrical strain gage on the opposite face. Cyclic compressive stresses were applied to the specimens and their corresponding strains monitored by the CNT strain gage as well as by the electrical strain gage. These strains were acquired by a commercial data acquisition system. With the results, it was possible to establish a relationship between the strain measured by the strain gauge and the piezoresistive response of the CNT sensor. This relation was exponential, and it was proved reproducible. The method used to manufacture the CNT sensor was considered viable, but it still requires improvements.